Implementation of Policy Program for Purchase of Rice Produced by Local Farmers by PNS in Ponorogo Regency - Candraningrum, Dice Erika (Prosiding Seminar, 2022)
This study purposes to describe and analyze the implementation of the policy of purchasing rice produced by local farmers by civil servants in Ponorogo Regency. The research location is at the Department of Agriculture, Food Security and Fisheries, Ponorogo Regency. The method used is descriptive qualitative method. The researcher used purposive sampling technique in determining the informants. Informants in this study were those who were technically involved and directly related to the implementation of the program. The data collection technique used the Miles and Huberman technique with the stages of data collection, data condensation, data presentation and drawing conclusions. The results showed that the policy implementation of the program to purchase rice produced by local farmers by civil servants in Ponorogo Regency was running quite optimally in the dimensions of policy content. In this case, in avoiding social conflicts between civil servants and farmers, the local government makes a legal umbrella in the form of a regent's regulation, farmers through the Gapoktan Association provide fairly good services to civil servants in providing rice based on the applicable rules.